Labour and Education Markets in Industry 4.0 - Matúšová Silvia; Kollár Vojtech (Sciendo, 2023)
Introduction: The current development of the world economy defined as the Fourth industrial revolution (Industry 4.0) is rather determined by a larger social change caused by the interconnection of the physical, virtual, and social worlds. It affects the market of products, production factors, sectors, services, education, research, social systems, the labour market, the education, and specialization, including the legal framework, and the use of digital technologies for production and education purposes.